Integration of Ecumenical Care Practices in Providing Holistic Care for Patient - Angelito E. Alvarado; Kei Julianja S. Paciente; Krissia Joi Ramirez; Diana Rose M. Reyes; Elmer Reyjohn L. Sagadraca; Maureen R. Salcedo; Jayferson M. Sales (Health Notions, 2021)
Ecumenical care practices is a sacred practice connected to chaplain practices that the nurse must provide to every patient. It is well defined that spiritual care practices are a component of holistic care, which is an integral part of the nursing profession, the ideal practice in giving care to the patient and considered the most crucial subset, which can easily be executed by nurses. The main objectives of this study is to determine how no significant relationship between the demographic profile and nurses ecumenical care practices and to assess the ecumenical practices of nurses in the provision of holistic care. The researchers used descriptive-correlational design. An online survey was done due to the limited interactions brought about by the pandemic. The researchers limited the study in the province of Isabela wherein they chose all the nurses in three (3) chosen hospitals, a private sectarian, non-private sectarian and government hospital. The researcher used Frequencies and Percentage, Weighted Mean, Mean Score, Chi Square Test and Anova Test as Statistical Treatment. Annova Test shows Significance F - value was less than 0.05. The null hypothesis is rejected. There is significant difference between the ecumenical care practices of nurses when they are grouped according to their profile variables. Chi Square shows significance C values for all the profile are greater than 0.05. The null hypothesis is accepted. There is no significant relationship between the level of integration of nurses of the ecumenical care and their profile sex, age, educational attainment, school graduated from, religion, patients each shift and time of shift. Ecumenical practices plays a vital role in every patient, in both sick and well so, it is important to respect the patient’s religion and integrate the practices in appropriate time and place. The researchers recommend that the nurses must be transcultural in addressing their patient to prevent bias and provide a good relationship with the patient for them to be comfortable and verbalize feelings to the nurse. Keywords: ecumenical care; holistic care; nursing practice